Efecto de una dieta a base de scomber scombrus l “caballa” sobre el perfil lipídico en pacientes ambulatorios con dislipidemias del hospital belén Trujillo-2010 - Guzmán Arangurí, Bertha Teófila (2012)
The aim of this research was to determine the effect of a diet with Scomber scombrus L. on the lipid profile in outpatients of Belen Hospital of Trujillo with dyslipidemia to see the possibility of preventing and treating this pathology and so avoiding circulatory problems related to arteriosclerosis, or strokes. By knowing that the blue fish such as the Scomber scombrus “Atlantic mackerel” “caballa” have a significant content of omega 3, there is a need to assess if a diet of Scomber scombrus L compared to a common diet plus atorvastatin for patients with dyslipidemia, could contribute to a significant variation on the lipid profile. We worked with 40 patients with dyslipidemia, divided into two groups of 20 individuals each randomly distributed: the control group and the experimental one. Administering to the control group a normal diet and treatment with atorvastatin and the experimental group was administered a diet designed on the basis of “Scomber scombrus L during a period of 3 months. Determining the basal values of the lipid profile and after 30, 60 and 90 days post treatment to both groups was made. The determinations were made with the enzymatic method of Wiener Lab. Atorvastatin decreased the values of: CT (26 %), TG (28 %), C-LDL (35 %),C-VLDL(28%) and increased HDL cholesterol (3.3 %).The diet of Scomber scombrus decreased the values of CT (41.5 %), TG (43 % ), C-LDL (41 %) ,C-VLDL(43%) and increased the values of C - HDL (21 %) in patients with dyslipidemia these effects were more significant with the diet of fish rather than with atorvastatin. (p<0.05). As a result, Scomber scombrus It constitutes a significant alternative in the initial treatment of dislipidemia for those with more moderately high levels of CT,C-LDL,C-VLDL and TG.